Characterization of phenolic compounds in Helichrysum melaleucumby high-performance liquid chromatography with on-line ultraviolet and mass spectrometry detection - Gouveia, Sandra C. (2021)
Helicrysum melaleucum is a medicinal plant traditionally used in the islands of the Macaronesia region for the treatment of respiratory diseases. In this work, the phenolic compounds of Helicrysum melaleucum plants collected in different geographical locations of Madeira Island and their morphological parts (total aerial parts, leaves, flowers and stems) were extracted and analyzed separately by high-performance liquid chromatography/electrospray ionization tandem mass spectrometry (HPLC-DAD/ESI-MS(n)). A total of 68 compounds were characterized based mainly on their UV and mass spectra. These included derivatives of O-glycosylated flavonoids (flavonol and flavones type), quinic acid, caffeic acid, lignans and polyphenols. The flowers were found to be the morphological part with higher variety of phenolic compounds. The large differences in the phenolic composition of plants collected from different geographical locations allowed the identification of a few components, such as pinoresinol and methoxylated flavone derivatives, likely to be useful as geographical markers. Also, these results promote further comparison of the bioactivities of the different samples analyzed. This paper marks the first report on the chemical analysis of Helichrysum melaleucum species.